Tinjauan Dramaturgi, Pengelolaan Kesan dalam Iklan Partai Politik "PAN PAN PAN" - Faruq Alhasbi; Rafi Ilham Hakim; Diva Allya; Ikhsannurdien Alfauzi (Pawarta: Journal of Communication and Da'wah, 2023)
Ahead of the 2024 Election, the virality of party jingles on social media has become interesting phenomenon in Indonesian politics. It caused the Election following by new voters with high use of social media. Therefore, political parties began to compete to attract the attention of these new voters in various ways, one of which was making the party's advertising content viral so that it became known to the community. The Partai Amanat Nasional (PAN) became one of the parties that succeeded in boosting electability after the viral jingle called PAN-PAN-PAN. There are some messages and agendas carried trough the song. So, researchers employing the constructivism paradigm to see how the party built political impression through jingles. A qualitative descriptive approach used to explain phenomena based on the perspective of Dramaturgical Theory, namely how impression created on front-stage and how the efforts made by the party behind the viral of PAN-PAN-PAN. As the result, the front stage especially tries to create an impression of being close to the millennial generation to get attention as new voters. Meanwhile, the jingle give the impression of being close to the community. That impressions supported by efforts to invite millennial public figures to join the party. The backstage also formed by the cadres' efforts to actualize the tagline, Bantu Rakyat.